Transient hyperammonemia associated with postictal state in generalized convulsion - Kuan-Ting Liu; Shih-Chia Yang; I.-Jeng Yeh; Tzeng-Jih Lin; Chi-Wei Lee (Kaohsiung Journal of Medical Sciences, 2011)
Previous studies revealed that transient hyperammonemia was noted after generalized convulsion. This study was undertaken to analyze the association between postictal state and serum ammonia levels. Adult patients presenting to the emergency department with seizures were included. Serum ammonia and other blood tests were compared between patients with full recovery of consciousness after generalized convulsion and those who had not completely regained consciousness. Patients who had not completely regained consciousness (7 of 7, 100%) had higher rate (p=0.035) of hyperammonemia compared with patients who had fully regained consciousness (4 of 10, 40%) and higher level of serum ammonia (246±96 μg/dL vs. 102±99 μg/dL, p=0.006). All patients who showed postictal consciousness level impairment on arrival at the emergency department had elevated serum ammonia at that time. Transient hyperammonemia is associated with postictal confusion.